PERAN GURU DALAM DETEKSI DINI ANAK BERKEBUTUHAN KHUSUS - Najma Fauziah Malik (Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 2022)
This research is motivated by the lack of parental communication during the initial assessment of early childhood in identifying children with special needs. This study was conducted to identify and describe the role of teachers in early detection of children with special needs. The research method used in this study is a qualitative method, with a case study approach, using data triangulation techniques. This research was conducted at PAUD SPS MAWAR III Anggadita Klari, with the number of subjects one person who is ABK with Autism. In this study, it was revealed that there was one PAUD SPS MAWAR III student who experienced obstacles in the development process. The characteristics of the child are lack of eye contact, likes to be alone, less able to get along with peers, parrots, suddenly cries alone and laughs alone for no reason, and the child's communication skills are lacking. On the other hand, these students have hyperactive behavior. The process carried out by teachers in early detection of special needs children is identifying their growth and development every month, observing children's behavior at school regularly, always involving children in learning activities, especially those related to group games, communicating with parents regarding symptoms of problems, consulting with experts. in this case the teacher involves psychologists and conducts diagnosis and information related to child development, as well as case conferences between professionals, teachers, and parents in order to get relevant treatment.